Larvicidal Effect of 96% Ethanol Extract of Lime (Citrus aurantifolia) Leaves with PEG 400 Diluent on Aedes aegypti Larvae - Dewi, Listiana Masyita; Mufidah, Fathin; Sutrisna, Em; Nurhayani, Nurhayani (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2024)
Larval control is remain the best method in reducing the high incidence of Dengue Fever, but temephos-resistance has also been reported. Lime (Citrus aurantifolia) leaves are thought to be a promising material to replace temephos. This study aim to identify the larvicidal effect of lime leaves ethanolic extract on Aedes aegypti. Lime leaves were extracted by maceration method and PEG 400 diluent was added as a dispersing agent. Total of 400 Aedes aegypti larvae at stages III-IV were enrolled. At 24 hours of observation, mortality rate of Aedes aegypti larvae in group with extract concentration of 0.3% and 0.4% was 92% and 100%, respectively. From post-hoc Mann Whitney test, p-value of <0.05 was only found when any study group were compared to negative control group. As as conclusion is 96% ethanol extract of lime leaves in addition of PEG 400 diluent has larvicide effect on Aedes aegypti larvae.